Análise numérica da influência de um conjunto de aletas com diferentes inclinações e posições em uma cavidade retangular preenchida por PCM em processo de fusão - Borahel, Rafael Da Silveira (Universidade do Vale do Rio dos Sinos, 2020)
Through the use of the finite volume method, the numerical study of the melting process of lauric acid contained in a finned rectangular cavity was conducted in this work. In the cavity, two longitudinal fins of rectangular shape are attached to the heated surface of the system under different inclinations. The aims of this study was (i) determine which metals are most suitable to be used in the fins; (ii) investigate the possibility of computational modeling of the fins to be performed in an idealized way, where the perimeter of the fins has identical temperatures to that of their base; (iii) analyze the melting process for a range of different inclinations (θ) used in the installation of the fins to the heated surface of the system; (iv) identify the existence or not of a more adequate inclination; (v) understand the effects caused by the different inclinations under the convection heat transfer that occurs inside the system; (vi) evaluate the effect of the vertical position of installation of the fins under the melting process intensified by them and (vii) determine the most suitable spacing to be allowed between the fins. To achieve the proposed objectives, two-dimensional transient numerical simulations, conducted in the commercial software ANSYS Fluent 19.2, were used to solve the proposed problem. In this software, unstructured computational meshes were used for the spatial discretization of the problem, while different time intervals were tested for temporal discretization. The mathematical model was composed by the differential equations of continuity, energy and momentum, plus the enthalpy-porosity method used to treat the lauric acid melting. The results obtained demonstrated that the implemented model is adequate for the proposed study and aluminum and copper are the most suitable materials for the fins, while steel was shown to be harmful to the heat transfer. The inclinations used in the installation of the fins influenced the process in different ways, proving that for the most initial and intermediate stages θ = 90° it considerably accelerated the melting, while higher θ values did better in the more advanced stages. Basically, there is no more suitable value for θ, but a range of possible values, which vary between 90 and 115°. In terms of performance, the lower the installation position of the fins, the faster the melting occurs.
Keywords: Armazenamento de energia térmica; Acúmulo de calor latente; Reservatório térmico aletado; Materiais de mudança de fase (PCM); Ácido láurico; Thermal energy storage; Latent heat accumulation; Finned thermal reservoir; Phase Change Materials (PCM); Lauric acid; ACCNPQ::Engenharias::Engenharia Mecânica